Impact of mineral fertilizers on common winter barley (Hordeum vulgare L.) agrophytocenosis development - Я. М. Мукан; О. С. Раченко (Plant Varieties Studying and Protection)
In 2011 to 2013 a study was completed for the impact of varying rates of fertilizing onto the indices of productivity for barley agrophytocenosis of Helios and Commandor, in particular, such its components as a number of productive stems, number of seeds per ear, potential biological activity of ear and photosynthetic apparatus. It is found that the level of spring barley agrophytocenosis productivity is subject both to varietal peculiarities and the rate of mineral fertilizer application. When applying N 60P 60K 60 і N 90P 90K 90 the highest potential and biological productivity of Helios and Commandor was recorder as compared against the control. Impact of varying application rates for fertilizers onto the components of ear biological productivity has been scrutinized. The qualitative composition of ear is a clear expression of variety phenotype and identifies the level of biological yield for spring barley. Application of N 60 P 60 K 60 і N 90 P 90 K 90 mineral fertilizers fairly increased the average leaf surface, photosynthetic lead capacity of varieties in 2 to 2.5 times, as well as FAR efficiency coefficient in 1.5 to 2.0 times as against control that thus contributed to the development of highest biological yield of Helios variety phytomass at the level of 14.9 to 15.0, grain – 7.8 to 8.0 ton per ha and, respectively, 12.7 and 7.5 tons per ha for Comandor variety.